Cyber-threat detection and analyzer - Lim, Gerald Jun Ji (2019)
Cyberthreats such as data breach, ransomware, Denial-of-Service (DoS)/Distributed-Denial-of-Service (DDoS) and many other types of attacks targeting everyone around the world is on the rise. The need of getting first hand information regarding those cyberthreats allows administrator or people to become the next victim by applying necessary prevention to the credentials or systems. In order to gather and organize that information from the internet and Deep Dark Web (DDW), a tool is developed to allow users to receive the latest information and eliminate duplicated information that gather from two or more source. With this tool, it will increase the efficiency of administrator to plan and prepare for cyberthreat with the gathered firsthand information and reduce the manhours to visit individual website to gather and cross-reference article creditability. In this report, the architecture, development and implementation of the Cyber-Threat Detection and Analyzer tool for gathering and organizing is explained.